Effect of stress, anxiety and depression on unstimulated salivary flow rate and xerostomia - Neda Gholami; Behrous Hosseini Sabzvari; Alireza Razzaghi; Shilan Salah (Tabriz University of Medical Sciences, 2017)
Background. Unstimulated salivary flow rate can be influenced by different factors. This study was undertaken to evaluate the effect of stress, anxiety and depression on unstimulated salivary flow rate in adults. Methods. A total of 247 adult subjects, randomly selected from patients referring to Zanjan Dental School, were included in this investigation. The study procedures consisted of collecting salivary samples (in 5 minutes), completing a form for feeling of xerostomia and completing Depression Anxiety Stress Scale (DASS) Questionnaire to assess the severity of stress, anxiety and depression. Based on the results, the patients were categorized in four groups: Low salivary flow rate plus xerostomia (group 1, n=60), normal salivary flow rate plus xerostomia (group 2, n=59), low salivary flow rate without xerostomia (group 3, n=60) and normal salivary flow rate without xerostomia (control group, n=68). Results. The frequencies of subjects with severe and major depression in groups 1, 2 and 3 were 31.4%, 11.7% and 8.5%, respectively, with 4.4% in the control group. The frequencies of subjects with severe stress in groups 1, 2 and 3 were 21.7%, 3.3% and 11.9%, respectively, with 1.5% in the control group. The frequencies of patients with severe anxiety in groups 1, 2 and 3 were 50%, 30% and 61.1%, respectively, with 4.4% in the control group. Stress, anxiety and depression exhibited a statistically significant relationship with unstimulated salivary flow rate and xerostomia (P<0.05). Conclusion. Stress, anxiety and depression can influence unstimulated salivary flow rate and lead to xerostomia.